Basic Image Analysis and Manipulation in ImageJ. Issue 1 (1st April 2013) - Hartig, Sean M.
Abstract: Image analysis methods have been developed to provide quantitative assessment of microscopy data. In this unit, basic aspects of image analysis are outlined, including software installation, data import, image processing functions, and analytical tools that can be used to extract information from microscopy data using ImageJ. Step‐by‐step protocols for analyzing objects in a fluorescence image and extracting information from two‐color tissue images collected by bright‐field microscopy are included. Curr. Protoc. Mol. Biol . 102:14.15.1–14.15.12. © 2013 by John Wiley & Sons, Inc.